2015
DOI: 10.1002/pat.3524
|View full text |Cite
|
Sign up to set email alerts
|

Tuning loading and release by modification of micelle core crystallinity and preparation

Abstract: Controlling and tuning the loading and release of incorporated drugs are vital parts of the advancement of drug delivery systems. Micelle systems that use core crystallinity to tune the loaded amount of hydrophobic molecules as well as their released amount were therefore developed. The conductive and electroactive aniline pentamer was incorporated into poly(ethylene glycol)-poly(ε-caprolactone) (PEG-PCL) micelles with semi-crystalline cores and poly(ethylene glycol)-poly(ε-decalactone) (PEG-PεDL) micelles wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 40 publications
3
18
0
Order By: Relevance
“…All polymers formed micelles ranging from 25 to 60 nm but only those incorporating DL were amorphous. The study showed that the critical aggregation concentration was higher for amorphous systems and that the loading of aniline pentamer was better in the amorphous vector [132,133]. A similar loading improvement in amorphous vectors for indomethacin was described by Alexander and co-workers [134].…”
Section: Cristallinitysupporting
confidence: 66%
“…All polymers formed micelles ranging from 25 to 60 nm but only those incorporating DL were amorphous. The study showed that the critical aggregation concentration was higher for amorphous systems and that the loading of aniline pentamer was better in the amorphous vector [132,133]. A similar loading improvement in amorphous vectors for indomethacin was described by Alexander and co-workers [134].…”
Section: Cristallinitysupporting
confidence: 66%
“…The glass transition temperature (T g ) of the hydrophobic segment has also been shown to have a direct effect on the CMC, micellar stability, and drug release rate [ 124 ]. At temperatures above T g , the CMC value increased with the temperature according to the following equation, ΔG 0 ∼ RTln(CMC), where G 0 and R are the Gibbs standard free energy and the universal gas constant, respectively, and the micelle core is in a liquid-like state.…”
Section: Characteristics Of Diblock Copolymersmentioning
confidence: 99%
“…Altering the properties of these copolymers, such as constituent chain length, hydrophilic-lipophilic balance (HLB), and charge, can even further alter a NP’s properties, including hydrodynamic size ( Wittgren et al, 1996 ), shell thickness ( Stubenrauch et al, 2006 ), and exposed peripheral functional groups ( Urbani et al, 2008 ; Pearson et al, 2016 ). This in turn allows further finetuning of drug delivery characteristics, such as API solubility, loading capacity, and release profiles ( Yan et al, 2011 ; Glavas et al, 2015 ). Altogether, this endows polymeric NPs with advantages similar to liposomes (e.g., easy encapsulation and high loading of lipophilic APIs, API protection, enhanced half-life and lowered blood clearance, sustained and controlled release, and the availability of readily modifiable surface end groups for targeting and stealth strategies) while also providing researchers with a more adaptable NP platform for various delivery needs.…”
Section: Nanomedicinementioning
confidence: 99%